Arrowhead - Eventhandler System - Sousa, José Pedro Neto Ferreira de Almeida e (2017)
The following document is the final report regarding PESTI – Internship Project of the Informatics Degree in Computer Science of ISEP. The Eventhandler project is englobed in the European Project Arrowhead. This framework allows the development of collaborative applications between several devices also known as Internet of Things or IoT. Its base foundation lies on the SOA architecture and currently offers services such as: Service Discovery, Authentication, Orchestration, Authorization and others. Each of which will be described in this document. Using the Eventhandler as an Arrowhead platform, Event Producer applications are able to register any kind of event such as: a temperature provided by sensor, warnings, errors, connection failures, etc. All this information must be stored in a database, local file or the Historian service provided by the Arrowhead Framework. Event Consumers can subscribe to the Eventhandler using a filter. Therefore, being able to receive in real time incoming events or access them through the permanent storage referred above. Besides implementing the Eventhandler locally, the main objective of this project is to also integrated this system within the Arrowhead cloud.